Prevalence of dolichoarteriopathies of the extracranial internal carotid artery by neck CTA in Mexican patients - Diana Camorlinga-Ornelas; Samuel Guillen-Ortega; Hilda Sarmiento-Martinez (Journal of the Mexican Federation of Radiology and Imaging)
Introduction: Dolichoarteriopathies of the extracranial internal carotid artery (EICA) are anatomical variants of the arterial course associated with alterations in the geometry and tortuosity of the vessel course. The reported prevalence varies widely, ranging from 10% to 70% in different studies. This study aimed to determine the prevalence of EICA dolichoarteriopathy types and subtypes in Mexican patients using neck computed tomography angiography (CTA). Material and methods: This cross-sectional study was conducted in patients who underwent neck CTA scans based on the referring physician´s clinical indication. An EICA dolichoarteriopathy variant was determined by reviewing CTA images in the axial, coronal, and sagittal planes. Laterality, type of dolichoarteriopathy (tortuosity, coiling, or kinking), and the kinking subtype were defined. Results: Two hundred seventy-one patients, 136 (50.2%) women and 135 (49.8%) men, were included. EICA dolichoarteriopathies were found in 151 of 271 patients with a prevalence of 55.7%. Dolichoarteriopathies were more common in older patients (p < 0.001). More than one type or subtype of EICA dolichoarteriopathies was found. Thus, 275 variants were found in 151 patients, with a comparable distribution on the right and left sides. Tortuosity was the most common type (n = 198, 72.0%), followed by kinking (n = 41, 14.9%) and coiling (n = 36, 13.1%). The subtypes were kinking A, 5.1% (n = 14), kinking B, 7.7% (n = 21), and kinking C, 2.2% (n = 6). Conclusion: We found a high prevalence (55.7%) of EICA dolichoarteriopathies. These were more frequent in older Mexican patients, and tortuosity was the most common. This study is the first to investigate the prevalence of types and subtypes of EICA dolichoarteriopathies in Mexican patients using neck CT.